Taxonomic notes on some Rubus species from China (Rosaceae) - Wang, Tao; Wang, Huan-Chong; Hou, Xue-Liang (Phytotaxa, 2024)
Based on studies on protologues, examination of herbaria specimens and field observation, taxonomic revisions on some Rubus species in China have been proposed. Rubus kuntzeanus and R. innominatus var. kuntzeanus are treated as new synonyms of R. innominatus. Rubus holadenus, R. tephrodes var. holadenus and R. farinaceus are treated as new synonyms of R. tephrodes. Rubus hui, R. reflexus var. hui, R. reflexus var. orogenes and R. irenaeus var. orogenes are treated as new synonyms of R. reflexus.